A polyolefin composite material and its preparation method and application
By using modified silicone microspheres loaded with lubricating oil in polyolefin materials, and improving interface compatibility through ultraviolet radiation and chemical modification treatment, the problem of poor hardness and wear resistance of polyolefin materials is solved, and the mechanical performance improvement of the material and the improvement of lubricating effect is achieved.
Patent Information
- Application Number
- CN202411678006.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Polyolefin materials have problems such as low surface hardness, low elastic modulus and bending strength, and poor anti-wear particle performance. The existing filling modification methods have poor interfacial compatibility and difficulty in uniform dispersing of small-molecular oils, resulting in a decline in mechanical properties.
Modified silicone microspheres loaded with lubricating oil are blended/filled with polyolefin matrix, and interface compatibility is improved by ultraviolet radiation and chemical modification treatment of silane coupling agent. The pores of silicone microspheres are loaded with small molecule lubricating oil to achieve good synergy between lubricating oil and silicone microspheres.
It significantly improves the hardness and mechanical properties of polyolefin composite materials, reduces the friction coefficient and wear rate, solves the problem of difficult uniform dispersion of small-molecular lubricants, realizes the synergistic effect of lubricating oil and silicone microspheres, and further improves the performance of the material.
Smart Images

Figure CN119161656B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to a polyolefin composite material and a preparation method and application thereof. Background Art
[0002] Polyolefin is a general term for a class of thermoplastic resins obtained by polymerization or copolymerization of alpha-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-pentene, and some cyclic olefins. It has the characteristics of low relative density, good chemical resistance, water resistance, good mechanical strength, and electrical insulation. It can be used for films, pipes, plates, various molded products, wires and cables, etc. It has a wide range of uses in agriculture, packaging, electronics, electrical, automobiles, machinery, daily sundries, etc. For example, ultra-high molecular weight polyethylene (UHMWPE) is widely used in various friction components due to its good self-lubricating properties and low water absorption.
[0003] However, polyolefins have disadvantages such as low surface hardness, low elastic modulus and bending strength, and poor anti-abrasive performance. Filling modification is a widely used method in the field of polymer modification, but due to the poor interface compatibility between fillers and polyolefin matrix, directly adding fillers can easily cause them to agglomerate in the polyolefin matrix, resulting in a decrease in mechanical properties; and some existing studies have also adopted the addition of small molecule oil substances for compounding, but small molecule oils are usually difficult to disperse evenly and stably in the polyolefin matrix, and oil substances as small molecule compounds will also affect the mechanical properties of the material. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and provide a polyolefin composite material and a preparation method and application thereof. Based on this, the first aspect of the present invention provides a polyolefin composite material, comprising melt-blended polyolefin and modified silicone microspheres loaded with lubricating oil; the preparation method of the modified silicone microspheres comprises the following process: ultraviolet irradiation of the silicone microspheres to form polar groups on their surfaces, and then chemically modifying them with a silane coupling agent to obtain the modified silicone microspheres; the silane coupling agent comprises vinyl.
[0005] The present invention uses modified silicone microspheres loaded with lubricating oil to blend / fill with a polyolefin matrix, wherein the silicone microspheres are used as spherical rigid fillers, which can greatly improve the hardness of the polyolefin composite material and thus enhance the mechanical properties, reduce the friction coefficient, and reduce wear; further, on this basis, in order to solve the technical problem of poor interface compatibility between the filler and the polyolefin matrix, the present invention chemically modifies the silicone microspheres to improve the interfacial bonding force between the two, and considering that silicone materials are generally difficult to directly chemically modify / chemically modify, the present invention also specifically performs ultraviolet radiation treatment before chemical modification to make the surface of the silicone microspheres carry polar groups, which is more conducive to subsequent chemical modification (silane coupling modification); on this basis, the present invention also utilizes the silicone microspheres The pores load the small molecule lubricant, further reducing the friction loss of the composite material. Moreover, since the silicone microspheres have good compatibility with the small molecule lubricant after UV irradiation and chemical modification, the small molecule lubricant can be prevented from diffusing out from the modified silicone microspheres and not easily extending into the polyolefin matrix, thereby solving the technical problem that the small molecule lubricant is usually difficult to disperse evenly and stably in the polyolefin matrix and affects the mechanical properties. Only when the modified silicone microspheres are worn or damaged during the process of friction and wear, the small molecule lubricant can seep out from the modified silicone microspheres, and the seeping small molecule lubricant can provide better lubrication, thereby further reducing friction and wear, and achieving good synergy between the small molecule lubricant and silicone microspheres.
[0006] In some preferred implementations, the silane coupling agent is one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triisopropoxy silane and vinyl methyl bis (trimethylsiloxy) silane. The effect is better when the silane coupling agent is vinyl trimethoxy silane or vinyl triethoxy silane.
[0007] In some preferred implementations, the lubricant is a poly-alpha-olefin oil. Specifically, it may be PAO2, PAO4, PAO5, PAO6, PAO7, or PAO8. Among them, the lubricant is PAO6, which has a better effect because it has a moderate viscosity and is not easy to overflow from the silicone microspheres during processing; moreover, it can have a good lubrication effect when wear and particle breakage occur. In addition, the lubricant may also include polyether synthetic oil and pure mineral oil.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned polyolefin composite material, comprising the following steps: melt-blending the polyolefin and the modified organic silicon microspheres loaded with lubricating oil to obtain the polyolefin composite material.
[0009] The preparation method of the organosilicon microspheres includes the following steps: hydrolyzing siloxane with water under acidic conditions, and then polycondensing under alkaline conditions to obtain the organosilicon microspheres. Specifically, the steps may be:
[0010] Water and hydrochloric acid (so that the pH of the system is 3-6, preferably pH 6) are added to a flask equipped with a condenser reflux tube, a stirring device and a thermometer, and then siloxane is added, stirred for 0.5 h-6 h (preferably 1 h) for hydrolysis reaction, and then ammonia water is added to adjust the pH to alkaline (pH 9-11, preferably pH 9), and stirring is continued for 1 h-10 h (preferably 1 h) for polycondensation reaction to obtain the silicone microspheres.
[0011] The mass ratio of siloxane to water is 1: (5-20), preferably 1: 10. The siloxane is at least one of methyltrimethoxysilane, methyltriethoxysilane, ethyltrichlorosilane, methyltrimethoxysilane, ethyltriethoxysilane and ethyltrichlorosilane.
[0012] The organosilicon microspheres obtained in the above process are separated, washed with water until the pH is neutral, and fully dried in an oven for subsequent ultraviolet irradiation-chemical modification process. The separation method can be one or any combination of filter paper filtration, filter cloth filtration or high-speed centrifugal separation; the water used for washing can be deionized water or distilled water, and the number of washing times is 3 to 5 times. The oven used can be a forced air drying oven or a vacuum drying oven, the drying temperature is 100°C-150°C, and the drying time is 4 h to 12 h.
[0013] The dried organic silicon microspheres are placed under an ultraviolet lamp for irradiation, the power of the ultraviolet irradiation is 250W-1000W; the time of the ultraviolet irradiation is 4 h-12 h; the distance between the light source (i.e., the ultraviolet lamp) and the organic silicon microspheres in the ultraviolet irradiation is 5 cm-10 cm.
[0014] The organic silicon microspheres after ultraviolet irradiation are chemically modified, and the chemical modification includes the following process: the organic silicon microspheres after ultraviolet irradiation are mixed with the silane coupling agent in an alcohol-water mixed solution, and heated until the alcohol boils, and the alcohol is condensed and refluxed, and the heating time is 1 h-6 h. The alcohol used may be methanol or ethanol, or a mixture of the two (when methanol is used, the silane coupling agent is vinyl trimethoxy silane, which has a better effect; when ethanol is used, the silane coupling agent is vinyl triethoxy silane, which has a better effect); in the alcohol-water mixed solution, the volume ratio of alcohol to water is between 95:5 and 85:15; the reflux temperature of the methanol used is 70°C, and the reflux temperature of the ethanol used is 90°C, which is higher than its boiling point; the amount of organic silicon microspheres added after ultraviolet irradiation (i.e., mass concentration) is 20 mL ethanol / 1 g organic silicon microspheres to 400 mL ethanol / 1 g organic silicon microspheres; the concentration of the silane coupling agent in the alcohol can be 0.5%-10% (mass fraction); and the stirring method is mechanical stirring with a stirring paddle or stirring with a magnetic stirring bar.
[0015] The chemically modified modified organosilicon microspheres are separated from the alcohol aqueous solution, washed with water or alcohol, and then placed in an oven for drying; the separation method can be one or a combination of filter paper filtration, filter cloth filtration or high-speed centrifugal separation; the water used for washing can be deionized water or distilled water, and the ethanol used can be anhydrous ethanol or ethanol with a water content not exceeding 25%; the number of washing times is 3 to 10 times; the oven used can be a forced air drying oven or a vacuum drying oven, the drying temperature is 90°C-120°C, and the drying time is 1 h to 6 h.
[0016] Subsequently, the dried modified silicone microspheres are loaded with lubricating oil, wherein the preparation method of the modified silicone microspheres loaded with lubricating oil comprises the following process: the modified silicone microspheres are mixed and stirred with the lubricating oil. The amount of the modified silicone microspheres added (i.e., the mass concentration) is 50 mL of lubricating oil / 1 g of modified silicone microspheres to 50 mL of lubricating oil / 5 g of modified silicone microspheres; after the modified silicone microspheres are added to the lubricating oil, they are first ultrasonically dispersed for 10 min-15 min, and then stirred for 12 h-24 h.
[0017] The modified silicone microspheres loaded with lubricating oil are separated, washed with water and ethanol, and then placed in an oven for drying; the water used for washing can be deionized water or distilled water, the ethanol used can be anhydrous ethanol or ethanol with a water content not exceeding 5%, and the washing times are 2 times each; the separation method can be one or any combination of filter paper filtration, filter cloth filtration or high-speed centrifugal separation.
[0018] The modified silicone microspheres loaded with lubricating oil are mixed with polyolefin, then banburying is performed, and then hot pressing is performed to obtain the polyolefin composite material. The banburying temperature is 210 °C; the specific process of hot pressing is: the banburying material is used as a sample, the sample is preheated for 10 min at a temperature of 210 °C, then pressurized for 10 min under a condition of 10 MPa, and then cold pressed for 15 min under a pressure of 10 MPa. The mass ratio of the modified silicone microspheres loaded with lubricating oil to the polyolefin is (2-30):100.
[0019] The third aspect of the present invention provides the use of the above polyolefin composite material in the preparation of friction pair components.
[0020] The beneficial effects of the present invention are as follows: the present invention uses ultraviolet radiation-chemically modified silicone microspheres and small molecule lubricating oils in synergistic combination for use in polyolefin composite materials, thereby solving the technical problems of existing filling processes, greatly improving the mechanical properties of polyolefin materials, and reducing the friction coefficient and wear rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Shown is the particle size distribution diagram of the organosilicon microspheres prepared in Example 1;
[0022] Figure 2 Shown is a scanning electron microscope image of the organosilicon microspheres prepared in Example 1;
[0023] Figure 3 Shown are infrared spectra of the modified organosilicon microspheres before and after loading PAO6 in Example 1;
[0024] Figure 4 Shown are thermogravimetric curves of the modified organosilicon microspheres without lubricating oil loaded prepared in Comparative Example 1 and the modified organosilicon microspheres loaded with lubricating oil prepared in Examples 1-2;
[0025] Figure 5 Shown are COF time curves of the polyolefin composite materials prepared in Examples 1-5 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0027] Example 1
[0028] A polyolefin composite material, the preparation method of which comprises the following steps:
[0029] (1) Add 500 mL of water and hydrochloric acid (to make the pH of the system 6) into a flask equipped with a condenser reflux tube, a stirring device and a thermometer, then add 5 g of methyltriethoxysilane and stir for 1 h for hydrolysis reaction. Then add ammonia water to adjust the pH to 9 and continue stirring for 1 h for polycondensation reaction to obtain organosilicon microspheres (the particle size distribution diagram is shown in FIG. Figure 1 As shown by Figure 1 It can be seen that the particle size of the prepared organosilicon microspheres is uniform; its scanning electron microscope image is as follows Figure 2 As shown by Figure 2 It can be seen that the prepared organosilicon microspheres do have a spherical structure and uniform particle size, which is consistent with Figure 1 After separation, the samples were washed with water until the pH value was neutral, and then dried in a vacuum drying oven (temperature: 120 °C, time: 6 h);
[0030] (2) 3 g of the dried organosilicon microspheres were placed under an ultraviolet lamp for irradiation, wherein the power of the ultraviolet irradiation was 200 W, the time of ultraviolet irradiation was 6 h, and the distance between the ultraviolet lamp and the organosilicon microspheres was 10 cm;
[0031] (3) Add 3 g of UV-irradiated organosilicon microspheres to 1000 mL of ethanol-water solution (the volume ratio of ethanol to water is 95:5), then add 10 mL of vinyltriethoxysilane, stir and heat until the ethanol boils (and keep heating for 4 h), condense the volatile ethanol and reflux it into the mixture to obtain modified organosilicon microspheres; after separation, wash with water, and then dry in a vacuum drying oven (temperature 120 °C, time 4 h);
[0032] (4) Add 2.5 g of the dried modified silicone microspheres into 50 mL of small molecule lubricant PAO6, disperse them by ultrasonication for 15 min, and then stir them for 4 h to obtain modified silicone microspheres loaded with PAO6 (the infrared spectra of the modified silicone microspheres before and after loading are shown in Figure 2). Figure 3 As shown by Figure 3 It can be seen that after loading PAO6, the 2856 cm -1 and 2924 cm -1 Two new characteristic peaks are derived from the CC group in the lubricating oil PAO6, proving that the modified silicone microspheres adsorbed the lubricating oil PAO6); after separation, they were washed twice with water and ethanol respectively, and then dried in a vacuum drying oven (temperature 90 ℃, time 2 h);
[0033] (5) 2 g of the dried modified silicone microspheres loaded with PAO6 were mixed with 20 g of ultra-high molecular weight polyethylene powder to obtain a mixed powder, and then the mixed powder was added to an internal mixer and internally kneaded at 210 °C. After internal kneading, a hot pressing treatment was performed, specifically: the internally kneaded material was used as a sample, preheated at 210 °C for 10 min, and then pressurized at 10 MPa for 10 min, and then the sample was kept under pressure at 10 MPa for 15 min to cool naturally; finally, an ultra-high molecular weight polyethylene composite material, i.e., the polyolefin composite material, was obtained.
[0034] Example 2
[0035] A polyolefin composite material, which differs from Example 1 in that the loaded lubricating oil is pure mineral oil Helitai SAE 10W-30, and the rest is the same as Example 1.
[0036] Example 3
[0037] A polyolefin composite material, which differs from Example 1 in that vinyl triethoxy silane is replaced by vinyl methyl bis (trimethylsiloxy) silane.
[0038] Example 4
[0039] A polyolefin composite material is disclosed. The difference between the embodiment 1 and the embodiment 1 is that the siloxane used in preparing the organosilicon microspheres is ethyltrimethoxysilane, and the rest is the same as the embodiment 1.
[0040] Example 5
[0041] A polyolefin composite material, which differs from Example 1 in that the loaded lubricating oil is PAO8.
[0042] Comparative Example 1
[0043] A polyolefin composite material, which is different from Example 1 in that the prepared modified organic silicon microspheres are not loaded with lubricating oil, and the rest is the same as Example 1.
[0044] Comparative Example 2
[0045] A polyolefin composite material, which differs from Example 1 in that no ultraviolet irradiation is performed; the rest is the same as Example 1.
[0046] Comparative Example 3
[0047] A polyolefin composite material is different from Example 1 in that: no ultraviolet irradiation and no modification with vinyltriethoxysilane are performed; the rest is the same as Example 1.
[0048] Comparative Example 4
[0049] A polyolefin composite material, which differs from Example 1 in that 3-aminopropyltriethoxysilane is used as a coupling agent to modify the organosilicon microspheres; the rest is the same as Example 1.
[0050] Effect performance test
[0051] The wear resistance and tensile properties of the polyolefin composite materials of Examples 1-5 and Comparative Examples 1-4 were tested as follows:
[0052] The mechanical properties test was carried out on a universal electronic testing machine. The size of the tensile specimen was 75 mm*10 mm*1 mm, the tensile rate was 50 mm / min, and the data average of five successfully tested samples was selected.
[0053] The friction performance was tested in a repeated mode on a UMT friction tester. The grinding head was made of bearing steel CCr15, the loading force was 20 N, the test time was 1 h, the frequency was 6 Hz, the distance was 10 mm, and the data average of three successfully tested samples was selected.
[0054] The results are shown in Table 1-2.
[0055] Table 1
[0056]
[0057] Table 2
[0058]
[0059] Figure 5 Shown are the COF time curves of the polyolefin composite materials of Examples 1-5 and Comparative Examples 1-4.
[0060] From Table 1-2 and Figure 5It can be seen that the tensile strength and elongation at break of the polyolefin composite materials of the present invention, i.e., Examples 1-5, are significantly better than those of Comparative Examples 1-4, and the friction coefficient and wear rate are significantly lower than those of Comparative Examples 1-4; it is shown that the polyolefin composite materials of the present invention have both good mechanical properties and friction properties or lubrication properties. However, Comparative Example 1 is not loaded with lubricating oil compared with the present invention, resulting in a certain gap in lubrication performance compared with the present invention; Comparative Example 2 is not subjected to ultraviolet irradiation compared with the present invention, resulting in very limited modification of the organosilicon microspheres by the vinyl silane coupling agent, which has a significant impact on the synergy between materials and the improvement of the interfacial bonding force, thus having a large gap in performance with the present invention; Comparative Example 3 has not undergone any chemical modification on the basis of Comparative Example 2, and its performance gap is even greater; Comparative Example 4 is not modified by a vinyl-containing silane coupling agent compared with the present invention, which also has a great impact on the chemical modification of the organosilicon microspheres, thereby affecting the synergy between materials and the interfacial bonding force, and also resulting in a certain gap in performance with the present invention.
[0061] By comparing Example 1 with Examples 2-5, it can be found that when poly-α-olefin oil is used as the lubricating oil in the system of the present invention for loading, the effect is better; and when PAO6 is further used, the effect can be further improved. In addition, when vinyl triethoxysilane (in the ethanol system) is used as the silane coupling agent for modification, the effect of the obtained polyolefin composite material is better.
[0062] also, Figure 4 The thermogravimetric curves of the modified organic silicon microspheres without lubricating oil prepared in Comparative Example 1 and the modified organic silicon microspheres with lubricating oil prepared in Examples 1-2 are shown; Figure 4 It can be seen that the lubricating oil PAO6 will be completely decomposed at 850 ℃. In Comparative Example 1, the modified silicone microspheres are not loaded with PAO6, but lose weight at 850 ℃, and the mass residual is 86.4%. This is because high temperature can degrade the molecular structure of the silicone microspheres. The mass residuals of Example 1 and Example 2 at 850 ℃ are 74.7% and 82.0%, indicating that the lubricating oil loaded in Example 1 and Example 2 is 11.7% and 4.4%, respectively.
[0063] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.
Claims
1. A polyolefin composite material, characterized in that: It includes melt-blended polyolefin and modified organosilicon microspheres loaded with lubricating oil; Preparation method of modified organic silicon microspheres The method comprises the following steps: ultraviolet irradiation is performed on the organosilicon microspheres to form polar groups on their surfaces, and then chemical modification is performed using a silane coupling agent to obtain the modified organosilicon microspheres; the silane coupling agent comprises vinyl.
2. The polyolefin composite material according to claim 1, characterized in that: The silane coupling agent is one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triisopropoxy silane and vinyl methyl bis (trimethylsiloxy) silane.
3. The polyolefin composite material according to claim 1, characterized in that: The lubricating oil is poly-alpha-olefin oil.
4. A method for preparing a polyolefin composite material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: melt-blending the polyolefin and the modified organic silicon microsphere loaded with lubricating oil to obtain the polyolefin composite material.
5. The preparation method according to claim 4, characterized in that: The chemical modification includes the following process: mixing the ultraviolet irradiated organosilicon microspheres with the silane coupling agent in an alcohol-water mixed solution, heating until the alcohol boils, condensing and refluxing the alcohol, and the heating time is 1 h-6 h.
6. The preparation method according to claim 4, characterized in that: The power of the ultraviolet irradiation is 250 W-1000 W; and / or, the time of the ultraviolet irradiation is 4 h-12 h; and / or, the distance between the light source in the ultraviolet irradiation and the organosilicon microspheres is 5 cm-10 cm.
7. The preparation method according to claim 4, characterized in that: The method for preparing the modified organic silicon microspheres loaded with lubricating oil comprises the following steps: mixing and stirring the modified organic silicon microspheres and the lubricating oil.
8. The preparation method according to claim 4, characterized in that: The preparation method of the organosilicon microspheres comprises the following steps: hydrolyzing siloxane with water under acidic conditions, and then polycondensing under alkaline conditions to obtain the organosilicon microspheres.
9. The preparation method according to claim 8, characterized in that: The siloxane is at least one of methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane and ethyltrichlorosilane; and / or, the alkaline condition is pH=9-11; and / or, the hydrolysis reaction time is 0.5 h-6 h; and / or, the acidic condition is pH=3-6; and / or, the mass ratio of the siloxane to water is 1:(5-20).
10. Use of the polyolefin composite material according to any one of claims 1 to 3 in the preparation of friction pair components.
Citation Information
Patent Citations
Single-pore hollow-structured organosilicon microspheres and preparation method thereof
CN103252202A
UHMW alloy pipe based on modified titanium metal and preparation method of UHMW alloy pipe
CN112194832A